2000
DOI: 10.1021/ie000376l
|View full text |Cite
|
Sign up to set email alerts
|

Aromatics/Aliphatics Separation by Adsorption:  New Sorbents for Selective Aromatics Adsorption by π-Complexation

Abstract: New sorbents for benzene/cyclohexane separation based on π-complexation were prepared by dispersion of transition metal salts on a high-surface-area substrate. PdCl 2 or AgNO 3 dispersed on SiO 2 gel exhibited high equilibrium adsorption ratios of benzene over cyclohexane. PdCl 2 loading of 0.88 g/g of SiO 2 showed the best benzene/cyclohexane ratio of 3.2. The heats of adsorption of benzene on these sorbents were in the range 7-12 kcal/mol and followed the rank order CuCl > PdCl 2 > AgNO 3 > AuCl 3 > PtCl 4 ,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
63
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 76 publications
(65 citation statements)
references
References 40 publications
(73 reference statements)
2
63
0
Order By: Relevance
“…This type of bonding is broadly referred to as -complexation. For example, CuCl, which is insoluble in water, has been considered in the power form for olefin/paraffin separation [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…This type of bonding is broadly referred to as -complexation. For example, CuCl, which is insoluble in water, has been considered in the power form for olefin/paraffin separation [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, this provides opportunities for tailoring and developing new adsorbents for processes where selective adsorption is needed, such as in the case of sulfur removal from fuels. Our group has already developed -complexation adsorbents for desulfurization Takahashi et al, 2002; Yang, 2003a, 2003b), olefin/paraffin, diene/olefin, and aromatics/aliphatics separations (Yang and Kikkinides, 1995;Rege et al, 1998;Huang et al, 1999aHuang et al, , 1999b Yang, 1997, 2000;Padin et al, 1999;Jayaraman et al, 2001;Takahashi et al, 2000Takahashi et al, , 2001. Hernández-Maldonado and Yang (2003a) found that both copper and silver exchanged faujasite type zeolites, Ag-Y and Cu(I)-Y, are excellent adsorbents for the removal of thiophene molecules from liquid hydrocarbon mixtures.…”
mentioning
confidence: 99%
“…[37][38][39] The second approach is to use a smallmolecule analogue of the binding site and apply spectroscopic and/or molecular modeling methods to study interactions between solutes and the analogue. 40,41 In previous studies, we used ethylpropionate (EP) as a small-molecule analogue of the acrylic ester's binding site. 6,7,28,42 Experimentally, we used infrared (IR) spectroscopy to measure shifts in the O-H stretching frequency that result from hydrogen bonding.…”
Section: Results and Discusssionmentioning
confidence: 99%